Erratum to: Cross-ancestry genome-wide association analysis of corneal thickness strengthens link between complex and Mendelian eye diseases (Nature Communications, (2018), 9, 1, (1864), 10.1038/s41467-018-03646-6) - Iglesias, A.I. (Nature Publishing Group, 2022)
10.1038/s41467-018-07819-1